Sustainability and recycling in fifteenth-century manuscripts - Ryley, H (2016)
This thesis examines the sustainability of fifteenth-century manuscripts. It analyses the durability of manuscripts, and the ways in which people recycled and reused their books. During the long fifteenth-century (here, 1375-1530), book production in England flourished, driven by increased demand for books. Yet while the fast-developing commercial book trade produced new books in great quantity, significantly, older books were also sustained, recycled and reused. Although there is awareness within medieval scholarship of recycled manuscript components, such as flyleaves, no sustained study has yet been undertaken into recycled and reused materials in fifteenth-century manuscripts, or into book production’s practices and processes of reuse. In addition, previous book history studies of recycling have focused on the book material reuse that followed the Dissolution. By contrast, this study offers a broader exploration of sustainable practices in fifteenth-century manuscript culture, as well as in-depth analysis of manuscript examples, to argue that book producers made and reused books in sustainable ways. The introduction outlines key concepts and relevant scholarship, such as studies that follow the material turn, and ecocriticism. The four chapters that follow address sustainability from different angles, focusing primarily on the evidence both in and written on books themselves. Chapter 1 explores the craftsmanship of parchment- making through contemporary recipes and physical evidence in manuscripts. Chapter 2 presents case studies of parchment reused sustainably in books, as off-cuts, quire guards, flyleaves, pastedowns, limp covers, and palimpsests. Chapter 3 surveys spaces reclaimed in books for opportunistic mark-making, in the form of doodles, jottings, and short verses. Chapter 4 presents three surveys of second-hand books and the inscriptions written onto their leaves. A conclusion draws together the findings. This thesis augments and nuances current scholarship by arguing that fifteenth-century reuse and recycling of book materials were customary aspects of book production and symptomatic of more widespread sustainability in manuscript culture.